2013
DOI: 10.4103/0974-8520.115440
|View full text |Cite
|
Sign up to set email alerts
|

Review of research works done on Tamra Bhasma [Incinerated Copper] at Institute for Post-Graduate Teaching and Research in Ayurveda, Jamnagar

Abstract: The metal, Tamra though mentioned in Ayurveda with a wide range of therapeutic utilities; is attributed with Ashta Maha Dosha. Hence, one should be cautious while using Tamra Bhasma. Considering the significance of Tamra in therapeutics, many studies have been carried out at different centers of India. Aim of the present study was to compile such available research works done on Tamra in the Department of Rasa Shastra and Bhaishajya Kalpana (RS and BK), IPGT and RA, Jamnagar and provide brief information about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…The finding is also in line with Chaudhari et al. [ 28 ]. who concluded that, when copper was processed as per ayurvedic texts to prepare Tamra Bhasma and subsequently consumed as per the ayurvedic texts, did not possess any toxic potential.…”
Section: Discussionsupporting
confidence: 93%
“…The finding is also in line with Chaudhari et al. [ 28 ]. who concluded that, when copper was processed as per ayurvedic texts to prepare Tamra Bhasma and subsequently consumed as per the ayurvedic texts, did not possess any toxic potential.…”
Section: Discussionsupporting
confidence: 93%
“…Intriguingly, the low-dose CuNP treatment averted the diabetes mellitus-induced myocardial lipid peroxidation as measured in the expression of diminution in cardiac TBARS. In fact, some studies suggest the anti-oxidant potential of copper 20,22,23 which might be a possible pathway of restoration of cardiac damages.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] Additionally, recent studies report a signicant anti-diabetic and cardio protective role of copper. [20][21][22][23] Furthermore, scientic literature has revealed the protective potential of copper to reduce the risk of recurrent ischemic stroke and cardiac injury. [24][25][26] Since the previous reports reveal the anti-platelet effect of copper, 27,28 it also has additional benecial effects including anti-inammatory, [29][30][31] anti-proliferative 32,33 and antioxidant potential.…”
Section: Introductionmentioning
confidence: 99%
“…2,9 This purely depends on media selected for incineration method adopted and the quantity of Rajata taken for incineration. 10 However the end point of all the experiments were determined by Bhasma Pareeksha. (Chief Desired Characteristics) RB was found to be black coloured smooth lusterless state due to transformation into compound form after incineration cycles.…”
Section: Discussionmentioning
confidence: 99%